MUSICAL TELEVISION OF BELARUS: 60 YEARS IN OWN IMAGE SEARCHING - Sushko Katerina O. (Mediamuzyka, 2016)
The paper is identified the key development stages of Belarusian musical television and the features of its function as a part of Central broadcasting system of the USSR and in the contemporary media space of the Republic of Belarus. On the basis of systematic studies of television content 1956-2016's, the author concluded that the origin path of development of domestic musical TV during the Soviet period (the formation of national identity, the emergence of unique genres) and serious crisis processes in the musical segment broadcasting after 1991 (Russian, British and American influence, secondary content, recreational function of the musical TV).